The effect of main characteristics of accounting information on supply chain performance, empirical study in Saudi Arabia - Mohamed Mukhtar ELsamani ELbasha; Abubkr Abdelraheem; Elfatih Bashir Idris Elbashir; Abdelmjeed Abdelrahim Ali Alajab; Omer Tajelsir Omer Elnour; Asaad Mubarak Hussien Musae (Decision Science Letters)
The study explored the influence of the main dimensions of accounting information (AI) relevance and reliability on supply chain performance (supply chain exchange information, supply chain collaboration, supply chain integration) at Noon e-commerce companies in Saudi Arabia. The researcher followed the descriptive analytical approach to describe the study variables based on previous studies and explore the study gap. The study adopted a questionnaire, of which 170 were collected. The data was analyzed using partial least squares (PLS) through structural equation modeling (SEM). The results indicated a positive effect of the relevance and reliability of AI on the dimensions of SC performance (SC exchange information, SC collaboration, SC integration), there is a positive effect of the reliability of AI on the dimensions of supply chain performance (SC exchange information, SC integration) and a negative effect of the reliability of AI on the SC collaboration parties. These results clarified the value and benefit of accounting information in improving supply chain performance.